A high thermal conductivity and low dielectric constant polyimide film and preparation method thereof

By modifying the polymerization reaction of porous boron nitride and polyimide film, the problems of insufficient thermal conductivity and high dielectric constant of the polyimide film are solved, and the effect of high thermal conductivity and low dielectric constant is achieved, and the electronic components are improved. Device stability and signal transmission efficiency.

CN116285347BActive Publication Date: 2024-12-20ANHUI GUOFENG PLASTIC +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310163700.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2024-12-20
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The thermal conductivity of existing polyimide films is insufficient, resulting in heat accumulation of electronic components, affecting stability and signal transmission, and a high dielectric constant leads to signal hysteresis.

Method used

Modified porous boron nitride, diamine monomer and dianhydride monomer in solvent polymerization, and after vacuum defoaming, casting film formation and thermal imidation treatment, a high thermal conductivity and low dielectric constant were prepared. Polyimide film. Modified porous boron nitride is surface modified by high-temperature calcination and electrostatic adsorption of cationic quaternary ammonium surfactant to improve its dispersion and compatibility in the polyimide matrix.

Benefits of technology

It significantly improves the thermal conductivity of the polyimide film, reduces the dielectric constant, has good mechanical properties, simple preparation process, and has good promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004095119660000081
    Figure BDA0004095119660000081
Patent Text Reader

Abstract

The invention discloses a high thermal conductivity and low dielectric constant polyimide film, which is obtained by polymerizing modified porous boron nitride with diamine monomers and dianhydride monomers in a solvent to obtain a polyamic acid solution, and then vacuum degassing, film casting, solvent removal and thermal imidization. The invention also discloses a method for preparing the high thermal conductivity and low dielectric constant polyimide film. The polyimide film prepared by the invention has high thermal conductivity, low dielectric constant and good mechanical properties, and has good promotion and use value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide, and in particular to a high-thermal-conductivity and low-dielectric-constant polyimide film and a preparation method thereof. Background Art

[0002] Polyimide (PI) refers to a type of polymer containing an imide ring (-CO-N-CO-) on the main chain. It is one of the organic polymer materials with the best comprehensive performance. It has outstanding comprehensive performance in flexibility, high temperature resistance, and insulation performance. It is widely used in electrical insulation, flexible circuit boards, flexible displays, 5G antennas, and heat dissipation materials. With the rapid development of science and technology, the trend of the integrated circuit industry towards low-dimensional, large-scale, and even ultra-large-scale integration is becoming increasingly obvious. When the size of electronic components is reduced to a certain scale, on the one hand, microelectronic components are in a high-density and high-speed operation state, which causes electronic components and integrated circuits to emit a large amount of heat and cannot be exported in time (the thermal conductivity of PI pure film is only 0.16W / (m·k)), which is very easy to accumulate heat, thereby affecting the stability, life and operation safety of electronic components, and limiting their application; on the other hand, the inductance-capacitance effect between the wiring of electronic components gradually increases, and the mutual influence of the wire current makes the signal hysteresis phenomenon very prominent, and the signal hysteresis time increases. The delay time is proportional to the dielectric constant of the interlayer insulating material (the dielectric constant of pure PI film is about 3.8). In the context of the in-depth development of ultra-large-scale integrated circuits, reducing the dielectric constant of interlayer materials has become an important means to reduce signal delay time. Therefore, it is very necessary to develop polyimide films with good thermal conductivity and low dielectric constant.

[0003] In order to improve the thermal conductivity of polymers, highly thermally conductive inorganic fillers are usually added to the polymer matrix. Boron nitride is often used as a thermally conductive filler, but its surface is relatively inert, difficult to modify, difficult to be compatible with polymers, and prone to agglomeration, which limits the use of boron nitride to improve the thermal conductivity of polymers. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a high thermal conductivity and low dielectric constant polyimide film and a preparation method thereof, which has high thermal conductivity, small dielectric constant, good mechanical properties, simple preparation process, and good promotion and use value.

[0005] The invention provides a high thermal conductivity and low dielectric constant polyimide film, which is obtained by polymerizing modified porous boron nitride with diamine monomer and dianhydride monomer in a solvent to obtain a polyamic acid solution, and then vacuum degassing, casting film, desolvation and thermal imidization.

[0006] The preparation method of the modified porous boron nitride is as follows: firstly, the porous boron nitride is calcined at high temperature in an air atmosphere to obtain the porous boron nitride with slightly oxidized surface, and then the surface of the porous boron nitride with slightly oxidized surface is modified by electrostatic adsorption using a cationic quaternary ammonium salt surfactant to obtain the modified porous boron nitride.

[0007] Preferably, the porous boron nitride has a particle size of 0.5-10 μm and a pore size of 20-80 nm.

[0008] Preferably, in the preparation method of the modified porous boron nitride, the high temperature calcination condition is: calcination at 700-1000° C. for 1-3 h.

[0009] Preferably, in the preparation method of the modified porous boron nitride, the specific steps of calcining the porous boron nitride at high temperature in an air atmosphere to obtain porous boron nitride with a slightly oxidized surface are: calcining the porous boron nitride powder at 700-1000°C for 1-3h in an air atmosphere, cooling, then adding deionized water for washing, centrifuging and drying to obtain the modified porous boron nitride.

[0010] Preferably, in the preparation method of the modified porous boron nitride, the specific steps of surface modification of the porous boron nitride with slightly oxidized surface by electrostatic adsorption using a cationic quaternary ammonium salt surfactant are as follows: dispersing the porous boron nitride with slightly oxidized surface in a methanol solution, then adding the cationic quaternary ammonium salt surfactant, stirring the reaction at room temperature for 1-3 hours, and then centrifuging and drying to obtain the product.

[0011] Preferably, the mass ratio of the porous boron nitride to the cationic quaternary ammonium salt surfactant is 1:(0.1-0.5).

[0012] Preferably, the cationic quaternary ammonium salt surfactant is at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride and octadecyltrimethylammonium bromide.

[0013] Preferably, the mass ratio of the modified porous boron nitride to the diamine monomer is (0.2-1.2):1, and the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).

[0014] Preferably, the diamine monomer is one or two of p-phenylenediamine, m-phenylenediamine and 4,4′-diaminodiphenyl ether; the dianhydride monomer is one or two of pyromellitic dianhydride and 3,3′,4,4′-biphenyltetracarboxylic dianhydride.

[0015] Preferably, the solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.

[0016] Preferably, the thickness of the polyimide film is 25-65 μm.

[0017] A method for preparing a polyimide film with high thermal conductivity and low dielectric constant comprises the following steps:

[0018] S1, dissolving a diamine monomer in a solvent to obtain a diamine solution; dispersing a modified porous boron nitride in a solvent to obtain a modified porous boron nitride dispersion; mixing the modified porous boron nitride dispersion with the diamine solution, stirring for reaction for 1-2 hours, and then adding a dianhydride monomer and stirring for reaction to obtain a polyamic acid solution;

[0019] S2, subjecting the polyamic acid solution to vacuum defoaming treatment, then casting into a film, heating in stages to remove the solvent and perform thermal imidization, and cooling to obtain the film.

[0020] Preferably, in S1, dianhydride monomer is added and stirred to react until the viscosity is 50000-150000 mPa·s.

[0021] Preferably, in S2, the specific steps of stepwise heating for desolvation and thermal imidization are: first desolvation at 100-120°C for 20-30min, then heat preservation at 150-180°C for 25-45min, heat preservation at 200-230°C for 25-45min, heat preservation at 250-280°C for 25-45min, and heat preservation at 350-380°C for 25-45min.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention calcines porous boron nitride at high temperature to make its surface slightly oxidized and negatively charged, and then adsorbs a cationic quaternary ammonium salt surfactant on its surface through electrostatic force to obtain modified porous boron nitride; then the modified porous boron nitride and a polymerized monomer of polyimide are subjected to in-situ polymerization reaction in a solvent to obtain polyamic acid, and finally a polyimide film is obtained through film casting and heat treatment. In the present invention, the surface modification of porous boron nitride by the cationic quaternary ammonium salt surfactant can improve the dispersibility and compatibility of porous boron nitride in a polyimide matrix, form a good heat conduction path, thereby improving the thermal conductivity of the polyimide film; in addition, the porous structure of porous boron nitride can improve the air volume rate of the polyimide film, thereby effectively reducing the dielectric constant of the polyimide film. The prepared polyimide film has high thermal conductivity, small dielectric constant, good mechanical properties, simple preparation process, and good promotion and use value. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is described in detail below through specific embodiments.

[0025] In the following examples and comparative examples, the particle size of porous boron nitride is 0.5-10 μm, and the pore size is 20-80 nm.

[0026] Example 1

[0027] Preparation of modified porous boron oxide:

[0028] (1) Weighing 30 g of porous boron nitride and placing it in a muffle furnace, calcining it at 900° C. for 2 h in an air atmosphere, then adding it to deionized water for ultrasonic dispersion, centrifuging it, and drying it to obtain porous boron nitride with slightly oxidized surface;

[0029] (2) Weigh 25 g of porous boron nitride with slightly oxidized surface and disperse it in a methanol solution, then add 7.5 g of hexadecyltrimethylammonium bromide, stir and react at room temperature for 2 h, then centrifuge and dry to obtain the product.

[0030] Preparation of high thermal conductivity and low dielectric constant polyimide film:

[0031] S1, 6g PDA and 14g ODA were dissolved in 210g DMAC to obtain a diamine solution; 15g modified porous boron nitride was added to 85g DMAC and dispersed in a dispersant for 2h to obtain a modified porous boron nitride dispersion; 35g of the modified porous boron nitride dispersion prepared above was weighed and added to the diamine solution, stirred for reaction for 1h, and then 27.37g PMDA was added in 3 times and stirred for reaction, with a time interval of 30min each time, and the reaction was carried out until the viscosity was 80000mPa·s to obtain a polyamic acid solution;

[0032] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and after cooling, a high thermal conductivity and low dielectric constant polyimide film with a thickness of 38 μm is obtained.

[0033] Example 2

[0034] Preparation of high thermal conductivity and low dielectric constant polyimide film:

[0035] S1, 6g PDA and 14g ODA were dissolved in 202g DMAC to obtain a diamine solution; 15g modified porous boron nitride was added to 85g DMAC and dispersed in a dispersant for 2h to obtain a modified porous boron nitride dispersion; 79g of the modified porous boron nitride dispersion prepared above was weighed and added to the diamine solution, stirred for reaction for 1h, and then 27.37g PMDA was added in 3 times and stirred for reaction, with a time interval of 30min each time, and the reaction was carried out until the viscosity was 80000mPa·s to obtain a polyamic acid solution;

[0036] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and after cooling, a high thermal conductivity and low dielectric constant polyimide film with a thickness of 38 μm is obtained.

[0037] Wherein, the preparation method of modified porous boron oxide is the same as that in Example 1.

[0038] Example 3

[0039] Preparation of high thermal conductivity and low dielectric constant polyimide film:

[0040] S1. Dissolve 6 g of PDA and 14 g of ODA in 194 g of DMAC to obtain a diamine solution; add 22.5 g of modified porous boron nitride to 127.5 g of DMAC and disperse in a dispersant for 2 h to obtain a modified porous boron nitride dispersion; weigh 135 g of the modified porous boron nitride dispersion prepared above and add it to the diamine solution, stir and react for 1 h, then add 27.37 g of PMDA in 3 times and stir and react, with a time interval of 30 min between each addition, and react until the viscosity is 80000 mPa·s to obtain a polyamic acid solution;

[0041] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and after cooling, a high thermal conductivity and low dielectric constant polyimide film with a thickness of 38 μm is obtained.

[0042] Wherein, the preparation method of modified porous boron oxide is the same as that in Example 1.

[0043] Comparative Example 1

[0044] Preparation of polyimide film:

[0045] S1. Dissolve 6 g of PDA and 14 g of ODA in 210 g of DMAC to obtain a diamine solution; add 15 g of porous boron nitride to 85 g of DMAC and disperse in a dispersant for 2 h to obtain a porous boron nitride dispersion; weigh 35 g of the porous boron nitride dispersion obtained above and add it to the diamine solution, stir and react for 1 h, then add 27.37 g of PMDA in 3 times, stir and react, and the time interval between each addition is 30 min, and react until the viscosity is 80000 mPa·s to obtain a polyamic acid solution;

[0046] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and a polyimide film with a thickness of 38 μm is obtained after cooling.

[0047] Comparative Example 2

[0048] Preparation of polyimide film:

[0049] S1. Dissolve 6 g of PDA and 14 g of ODA in 202 g of DMAC to obtain a diamine solution; add 15 g of porous boron nitride to 85 g of DMAC and disperse in a dispersant for 2 h to obtain a porous boron nitride dispersion; weigh 79 g of the porous boron nitride dispersion obtained above and add it to the diamine solution, stir and react for 1 h, then add 27.37 g of PMDA in 3 times, stir and react, the time interval between each addition is 30 min, react until the viscosity is 80000 mPa·s, and obtain a polyamic acid solution;

[0050] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and a polyimide film with a thickness of 38 μm is obtained after cooling.

[0051] Comparative Example 3

[0052] Preparation of polyimide film:

[0053] S1, 6g PDA and 14g ODA were dissolved in 194g DMAC to obtain a diamine solution; 22.5g porous boron nitride was added to 127.5g DMAC and dispersed in a dispersant for 2h to obtain a porous boron nitride dispersion; 135g of the porous boron nitride dispersion prepared above was weighed and added to the diamine solution, stirred for reaction for 1h, and then 27.37g PMDA was added in 3 times and stirred for reaction, with a time interval of 30min each time, and the reaction was carried out until the viscosity was 80000mPa·s to obtain a polyamic acid solution;

[0054] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and a polyimide film with a thickness of 38 μm is obtained after cooling.

[0055] Comparative Example 4

[0056] Preparation of polyimide film:

[0057] S1, 6g PDA and 14g ODA were dissolved in 216g DMAC, and then stirred for 2h to obtain a diamine solution; then 27.37g PMDA was added in 3 times with a stirring reaction, each time interval of 30min, and the reaction was carried out until the viscosity reached 80000mPa·s to obtain a polyamic acid solution;

[0058] S2. The polyamic acid solution is subjected to vacuum defoaming treatment in a -1Mpa oven, and then cast into a film on a glass plate of an automatic coating machine, and then the solvent is removed at 110°C for 25 minutes, kept warm at 160°C for 30 minutes, kept warm at 210°C for 30 minutes, kept warm at 260°C for 30 minutes, and kept warm at 360°C for 30 minutes, and a polyimide film with a thickness of 38 μm is obtained after cooling.

[0059] Test example

[0060] The thermal conductivity, dielectric constant and mechanical properties of the polyimide films prepared in Examples 1-3 and Comparative Examples 1-4 were tested. The results are shown in Table 1.

[0061] Thermal conductivity test: Tested using Hot Disk ISO 22007-2 standard;

[0062] Mechanical properties test: Tested according to GB / T 1040.3-2006 standard;

[0063] Dielectric constant test: Tested according to GB / T 1409-2006 standard.

[0064] Table 1 Thermal conductivity, dielectric constant and mechanical properties of polyimide films

[0065]

[0066] As can be seen from Table 1, compared with Comparative Example 4, the thermal conductivity of Examples 1-3 and Comparative Example 1-3 in which porous boron nitride fillers are added is improved; however, compared with Comparative Example 1-3, the thermal conductivity of Example 1-3 is significantly improved, which may be because the dispersion of the porous boron nitride in the matrix of the present invention is improved, reducing its agglomeration in the polyimide, forming a good heat conduction path, and thus improving its thermal conductivity. Moreover, the tensile strength in Examples 1-3 of the present invention decreases less, which can ensure the normal use of the polyimide film. In addition, compared with Comparative Example 4, the dielectric constant of Examples 1-3 and Comparative Example 1-3 in which porous boron nitride fillers are added is reduced, which may be because the porous structure of the porous boron nitride can increase the air volume rate of the polyimide film, thereby effectively reducing the dielectric constant of the polyimide film.

[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high thermal conductivity and low dielectric constant polyimide film, characterized in that: The modified porous boron nitride is polymerized with a diamine monomer and a dianhydride monomer in a solvent to obtain a polyamic acid solution, which is then subjected to vacuum degassing, film casting, solvent removal and thermal imidization to obtain the polyamic acid solution; The preparation method of the modified porous boron nitride is as follows: firstly, the porous boron nitride is calcined at high temperature in an air atmosphere to obtain the porous boron nitride with slightly oxidized surface, and then the surface of the porous boron nitride with slightly oxidized surface is modified by electrostatic adsorption using a cationic quaternary ammonium salt surfactant to obtain the modified porous boron nitride; The porous boron nitride has a particle size of 0.5-10 μm and a pore size of 20-80 nm.

2. The high thermal conductivity and low dielectric constant polyimide film according to claim 1, characterized in that: In the preparation method of the modified porous boron nitride, the high temperature calcination condition is: calcination at 700-1000° C. for 1-3 hours.

3. The high thermal conductivity and low dielectric constant polyimide film according to claim 1, characterized in that: In the preparation method of the modified porous boron nitride, the specific steps of using a cationic quaternary ammonium salt surfactant to modify the surface of the porous boron nitride with slight oxidation on the surface by electrostatic adsorption are as follows: dispersing the porous boron nitride with slight oxidation on the surface in a methanol solution, then adding the cationic quaternary ammonium salt surfactant, stirring the reaction at room temperature for 1-3 hours, and then centrifuging and drying to obtain the product.

4. The high thermal conductivity and low dielectric constant polyimide film according to claim 3, characterized in that: The mass ratio of the porous boron nitride to the cationic quaternary ammonium salt surfactant is 1:(0.1-0.5); the cationic quaternary ammonium salt surfactant is at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, and octadecyltrimethylammonium bromide.

5. The high thermal conductivity and low dielectric constant polyimide film according to claim 1, characterized in that: The mass ratio of the modified porous boron nitride to the diamine monomer is (0.2-1.2):1, and the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).

6. The high thermal conductivity and low dielectric constant polyimide film according to claim 1, characterized in that: The thickness of the polyimide film is 25-65 μm.

7. A method for preparing a high thermal conductivity and low dielectric constant polyimide film according to any one of claims 1 to 6, characterized in that: The steps include: S1, dissolving a diamine monomer in a solvent to obtain a diamine solution; dispersing a modified porous boron nitride in a solvent to obtain a modified porous boron nitride dispersion; mixing the modified porous boron nitride dispersion with the diamine solution, stirring for reaction for 1-2 hours, and then adding a dianhydride monomer and stirring for reaction to obtain a polyamic acid solution; S2, subjecting the polyamic acid solution to vacuum defoaming treatment, then casting into a film, heating in stages to remove the solvent and perform thermal imidization, and cooling to obtain the film.

8. The method for preparing a polyimide film with high thermal conductivity and low dielectric constant according to claim 7, characterized in that: In S1, add dianhydride monomer and stir to react until the viscosity reaches 50000-150000 mPa·s.

9. The method for preparing a polyimide film with high thermal conductivity and low dielectric constant according to claim 7, characterized in that: In S2, the specific steps of desolvation and thermal imidization by staged heating are: first desolvation at 100-120°C for 20-30 min, then keeping warm at 150-180°C for 25-45 min, keeping warm at 200-230°C for 25-45 min, keeping warm at 250-280°C for 25-45 min, and keeping warm at 350-380°C for 25-45 min.

Citation Information

Cited By

  • Preparation method of polyimide fluorinated graphene composite film with bidirectionally adjustable dielectric constant

    CN120842631A